2022
DOI: 10.3389/fgene.2022.1000339
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive bioinformatics analysis reveals the prognostic value, predictive value, and immunological roles of ANLN in human cancers

Abstract: Anillin (ANLN) is a unique scaffolding, actin-binding protein, which is essential for the integrity and ingression of the cleavage furrow. It is mainly involved in the cytokinesis process, while its role in various tumors has not been fully addressed and remains largely elusive. To provide a thorough perspective of ANLN’s roles among diverse malignancies, we conducted a comprehensive, pan-cancer analysis about ANLN, including but not limited to gene expression levels, prognostic value, biological functions, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…Another of our hub genes, Anillin (ANLN) , which is essential for cytokinesis, is elevated in the early stages of 17 cancers, and in more than ten tumors, higher expression of ANLN is associated with a poorer prognosis. 62 In our study, we found for the first time that AML patients with high levels of beta-catenin had higher expression of the ANLN gene.…”
Section: Discussionsupporting
confidence: 48%
“…Another of our hub genes, Anillin (ANLN) , which is essential for cytokinesis, is elevated in the early stages of 17 cancers, and in more than ten tumors, higher expression of ANLN is associated with a poorer prognosis. 62 In our study, we found for the first time that AML patients with high levels of beta-catenin had higher expression of the ANLN gene.…”
Section: Discussionsupporting
confidence: 48%
“…comp-genomics.org/) provides free access to explore gene expression and tumor immune infiltration in TCGA cohorts. Referring to previous research, we assessed the correlation of DSCC1 expression with myeloid-derived suppressor cells (MDSCs) and natural killer (NK) T cells (NKT/T cell NK) infiltration levels under the "immune" module [10]. Additionally, the single-sample GSEA algorithm, with gene sets consisting of markers of individual immune cells, enabled us to estimate the correlation of DSCC1 with the infiltration of 24 types of tumor-infiltrating lymphocytes (TILs) [11].…”
Section: Correlation Between Dscc1 Expression and Tumor Immunitymentioning
confidence: 99%